The moderating effect of personality in the relationship between job demand and job control on workplace bullying: A study among nurses in Jordan - Al Muala, Imad Mohmad Atwan (2013)
This study examined the factors influencing workplace bullying among nurses in the public hospitals in Jordan. The objective of the study was to examine the influence of job demand and job control on workplace bullying among nurses in Jordan. The role of personality as the moderating factor in this relationship was also examined. The study utilized a survey method and questionnaires were distributed to a sample of 750 nurses at one of the biggest public hospitals in Jordan. The data was analysed using regression analysis techniques, and hierarchal regression analysis. The study found that the level of workplace bullying among nurses as being high. The study also found a positive and significant relationship between job demand and workplace bullying. The study also found that there appeared a significantly negative relationship between job control and workplace bullying. Personality too appeared as partial moderator in the relationship between job demand and job control on workplace bullying. Personality traits of conscientiousness and openness to experience were found to moderate the relationship between job control and workplace bullying. Other than that, emotional stability was found playing a role in moderating the relationship between work pressure and workplace bullying. The finding of this study strengthens earlier research findings regarding the importance of personality in influencing workplace bullying. It can thus be concluded, that understanding job demand and job control factors in the workplace and managing them effectively can help reduce incidents of bullying among nurses in Jordanian hospitals. Furthermore, the different personality traits of nurses and the interaction of these traits with job demand and job control factors, show the workplace bullying differences among nurses in the Jordanian hospitals